Lifestyle measures for primary prevention of T2 Diabetes Mellitus (T2DM) - Ahmed, M S A Mansur (Indian Journal of Community Health, 2014)
Worldwide, the number of adults with diabetes was 285 million in 2010 and it will be 439 million in the year 2030. Although the genes we inherit may influence the development of type 2 diabetes, they take a back seat to behavioral and lifestyle factors. Data from the Nurses’ Health Study suggest that 90 percent of type 2 diabetes in women can be attributed to five such factors: excess weight, lack of exercise, a less-than-healthy diet, smoking, and abstaining from alcohol. From this data it can be said that up to 90 percent of diabetes prevention is possible with behavioral and lifestyle factors intervention. This intervention should be given to the people through primary prevention. The purpose of primary prevention is to limit the number of people who develop a disease by controlling causes and risk factors for the disease.